T. S. Palmer papers - Palmer, T. S. (Theodore Sherman), 1868-1955.
Chiefly correspondence of Palmer with fellow ornithologists and with persons interested in the field of ornithology. Relates chiefly to Palmer's work as secretary of the American Ornithologists' Union from 1917 to 1937 and to his support of federal and state wildlife conservation measures. Also includes diaries, memorandum books, speeches, articles, printed matter, scrapbooks, photographs, and other papers.
Library of Congress Prints and Photographs Division.
Naturalist, author and ornithologist.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Ornithologists' Union; Conservation of natural resources; Ornithology; Ornithology -- Societies, etc; Authors; Naturalists; Ornithologists